Influence of laboratory conditions on two species Dictyotaceae family (Phaeophyceae): Diterpenoid profile and physiological response - Obando, Johana Marcela Concha; dos Santos, Thalisia Cunha; Fortes, Rafael da Rocha; Bernardes, Marcelo; Nascimento, Nívia; Villaça, Roberto Campos; Teixeira, Valeria Laneuville; Barbarino, Elisabete; Cavalcanti, Diana Negrão (Frontiers in Marine Science, 2023)
The seaweed Dictyotaceae family has a great wealth of diterpenes with important biological activities. Information on these diterpenes qualitative and quantitative aspects in conjunction with physiological data and abiotic parameters are essential to obtain an effective algal culture system that is a sustainable resource. In this study, the diterpene profile of Dictyota menstrualis and Canistrocarpus cervicornis were analyzed as a function of in vitro maintenance time and the influence of culture medium. The algae were collected in the state of Rio de Janeiro and subjected to an acclimation period in the laboratory. Then, the species were acclimated in aquaria containing seawater from the collection sites. Then biomass algal was divided into (i) control experiment (CC): Growth in sterilized seawater; (ii) enriched experiment (EE): Growth in sterilized seawater enriched with Provasoli/2. Triplicate experiments were maintained in vitro (2.4% m/v), and the medium was changed every 7 days. Diterpenes were monitored using dichloromethane extracts from dried algae: (a) collected in the field, (b) after the acclimation period, and (c) from experimental units taken every 7 days for a total of 21 days. Among the main results, we found response variables such as specific growth rate (SGR); moreover, positive data were obtained for the alga C. cervicornis in CC, and this was evident showing after 7 days of cultivation in the experimental control unit (CU). For D. menstrualis, the SGRs for the treatments were negative at the monitored time, which was due to biomass losses, frond breakage, and rapid decomposition of some individuals that did not withstand the stress conditions during their collection. The analysis of the chemical profile by GC-MS made it possible to monitor 12 diterpenes and one sterol in the alga D. menstrualis and 7 diterpenes in C. cervicorni. The correlations found by Generalized Linear Models (GLMs) and redundancy analysis (RDA) statistical analyzes between the diterpene profile with the monitored variables (Nitrate, ammonia and pH), showed correlations for 10 diterpenes of the species D. menstrualis and 1 of the C. cervicornis, our analyses are important for the discussion of metabolic plasticity of the Dictyotaceae family